Proceedings of the 2011 International Conference on Informatics, Cybernetics, and Computer Engineering (ICCE2011) November 19-20, 2011, Melbourne, Australia Volume 1: Intelligent Control and Network Communication - Jiang, Liangzhong; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
The volume includes a set of selected papers extended and revised from the International Conference on Informatics, Cybernetics, and Computer Engineering. Intelligent control is a class of control techniques, that use various AI computing approaches like neural networks, Bayesian probability, fuzzy logic, machine learning, evolutionary computation and genetic algorithms. Intelligent control can be divided into the following major sub-domains: Neural network control Bayesian control Fuzzy (logic) control Neuro-fuzzy control Expert Systems Genetic control Intelligent agents (Cognitive/Conscious control) New control techniques are created continuously as new models of intelligent behavior are created and computational methods developed to support them. Networks may be classified according to a wide variety of characteristics such as medium used to transport the data, communications protocol used, scale, topology, organizational scope, etc. ICCE 2011 Volume 1 is to provide a forum for researchers, educators, engineers, and government officials involved in the general areas of Intelligent Control and Network Communication to disseminate their latest research results and exchange views on the future research directions of these fields. 90 high-quality papers are included in the volume. Each paper has been peer-reviewed by at least 2 program committee members and selected by the volume editor Special thanks to editors, staff of association and every participants of the conference. It$1 (Bs you make the conference a success. We look forward to meeting you next year.s
From the content: A trust management model based on reputation for virtual community -- Fault Location of Aircraft Cable Based on One-terminal Electrical Quantities -- Application Research on Computer Rank Examination Basing on Data Mining -- Popular misunderstandings and improvement strategies for network marketing -- Research of RFID Service frame based on OSGi -- Analysis of the radiation mode of the leaky coaxial cable with vertical slots.
Keywords: Engineering; Management information systems; Engineering; Computational Intelligence; Business Information Systems; e-Commerce/e-business.